TỔNG HỢP VẬT LIỆU MAO QUẢN TRUNG BÌNH SBA-15 CHỨA NHÓM THIOL (-SH) VÀ HOẠT TÍNH HẤP PHỤ ION Pb2+ TRONG DUNG DỊCH NƯỚC - Đức, Hoàng Văn; Anh Thư, Nguyễn Thị; Thịnh, Phạm Duy; Phương, Đặng Tuyết; Phú, Nguyễn Hữu (Vietnam Journal of Chemistry, 2012)
Mesoporous thiol-functionalized SBA-15 silicas (HS-SBA-15) have been directly synthesized by co-condensation of tetraethyl orthosilicate (TEOS) and 3-mercaptopropyltrimethoxysilane (MPTMS) with triblock copolymer P123 as-structure-directing agent under hydrothermal condition. The sample was characterized by EDX, IR and N2 adsorption–desorption measurement. The sorption behaviors of Pb2+ on the sample were studied. Freundlich isotherm was found to describe the sorption data better than Langmuir isotherm and pseudo second order kinetic model could fit the rate equation of that Pb2+ad sorption on HS-SBA-15 solid.